(3JYdjb Ydi GdchcH GdSGWYs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg agPG JYdjb MSf GdSjGb s
(3BNQgG (B:s
(3eUdjkG Ydi fHi ecGQe GdNdb Hg hJJe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs